YOUTHCENTER DI KEBUMEN SEBAGAI WADAH PENGEMBANGAN KREATIVITAS REMAJA DENGAN PENDEKATAN PSIKOLOGI ARSITEKTUR - Fahlevi Ismail; Amin Sumadyo; Fauzan Ali Ikhsan (ARSITEKTURA, 2016)
There are many communities, teen clubs and events held in the city of Kebumen, this is a sign that the local youth have the potential to show the creativity and existence. This phenomenon needs to be balanced with the provision of a wide range of facilities to accommodate youth activities such as sports facilities, arts facilities and community facilities. The facility in the city of Kebumen still minimal and insufficient for the scale of the city. Design Youth Center in Kebumen City aims to get the design of the building to facilitate sports activities, arts and community activities into the shape of the building is able to accommodate youth to enhance the creativity of teenagers. Design issues are: how the expression of space and form of the building that can accommodate the adolescent approach to Architectural Psychology is then translated into the design of the container Youth Center in Kebumen. The method used is a method of designing the architecture, from the collection of data was then analyzed by functional programming, programming performance and architectural analysis. Concept design: Architectural Psychology applied to the expression of space and forms building Youth Center is expected to bring the design of the building is able to accommodate adolescent psychology to be more creative in the activities in it. Keywords: Adolescent, Architecture Psychology (psychophysical aspects), Creativity, Kebumen, Youth Center.